The child sexual abuse crisis of the Church in Spain: case study on the genesis, methodology and contents of the report Para dar luz (To Give Light) by the Spanish Episcopal Conference (2023) - de la Cierva, Yago (Church, Communication and Culture, 2025)
In December 2023, in the midst of a harsh controversy that had been dragging on for years, the Spanish Episcopal Conference published the report Para dar luz, in which it showed the results of the investigations carried out to find out the real dimensions of sexual abuse of minors committed by Catholic clergy in Spain. This crisis management and communications’ case study analyzes the genesis of this report, explains its methodology, and summarizes its main results in order to answer the following questions: what moved the bishops to make that decision and in which circumstances; what were the main clauses of the agreement with the law firm; and what impact the report had on public opinion. From this analysis, some conclusions can be drawn from the communication’s point of view, useful for Church authorities considering the opportunity of commissioning a similar report and for their communication teams.